Mesophotic Depth Gradients Impact Reef Fish Assemblage Composition and Functional Group Partitioning in the Main Hawaiian Islands - Asher, Jacob; Williams, Ivor D.; Harvey, Euan S. (Frontiers in Marine Science, 2017)
Mesophotic coral ecosystem (MCE) research has increased considerably in recent years, as MCEs may provide partial insulation from the effects of climate change, localized anthropogenic stressors, and may dampen fishing pressures for target species depleted in shallower waters. However, few studies have examined coral reef fish assemblages and functional groups across shallow water to mesophotic depth gradients. In the Main Hawaiian Islands, we investigated coral reef fish communities between 0 and 100 m using baited remote underwater stereo-video. While significant community shifts were detected when transitioning from shallow water to mesophotic depths, relative abundance and species richness remained highest between 0 and 30 m. Mobile invertivores and generalist macropiscivores were exceptions, recording higher abundance and richness values in deeper waters. Depth, habitat complexity, and percent cover of unconsolidated sediment and macroalgae were the main reef fish community drivers in multivariate regression and distance-based linear models. Finally, several target species were more abundant and/or larger in deeper waters, suggesting stock assessment and resource management strategies are incomplete without the incorporation of mesophotic portions of stocks.